Comparison of total electron content predicted by IRI with that measured over Ankara - Özean, Osman; Ünal, Ïbrahim (My University, 2001)
The total electron content (TEC) is a very important parameter for the systems that use transionospheric radio waves. In this paper, TEC measurements obtained with Faraday technique at Ankara (geogr. lat. 40°N, geogr. long. 33°E, geomagn. lat. 36.9°N, dip angle 56.7°) are compared with the TEC obtained by using the International Reference Ionosphere (IRI) model to check the performance of IRI for predicting TEC over this station. The measurements have been taken between October 1975 and June 1976 during low solar activity period. In general, the IRI model was found to give good predictions except for spring equinox and summer solstice time.